Lack of Adrenomedullin Results in Microbiota Changes and Aggravates Azoxymethane and Dextran Sulfate Sodium-Induced Colitis in Mice - Martínez-Herrero, Sonia; Larrayoz, Ignacio M.; Narro-Íñiguez, Judit; Villanueva-Millán, María J.; Recio-Fernández, Emma; Pérez-Matute, Patricia; Oteo, José A.; Martínez, Alfredo (Frontiers in Physiology, 2016)
The link between intestinal inflammation, microbiota, and colorectal cancer (CRC) is intriguing and the potential underlying mechanisms remain unknown. Here we evaluate the influence of adrenomedullin (AM) in microbiota composition and its impact on colitis with an inducible knockout (KO) mouse model for AM. Microbiota composition was analyzed in KO and wild type (WT) mice by pyrosequencing. Colitis was induced in mice by administration of azoxymethane (AOM) followed by dextran sulfate sodium (DSS) in the drinking water. Colitis was evaluated using a clinical symptoms index, histopathological analyses, and qRT-PCR. Abrogation of the adm gene in the whole body was confirmed by PCR and qRT-PCR. KO mice exhibit significant changes in colonic microbiota: higher proportion of δ-Proteobacteria class; of Coriobacteriales order; and of other families and genera was observed in KO feces. Meanwhile these mice had a lower proportion of beneficial bacteria, such as Lactobacillus gasseri and Bifidobacterium choerinum. TLR4 gene expression was higher (p<0.05) in KO animals. AM deficient mice treated with DSS exhibited a significantly worse colitis with profound weight loss, severe diarrhea, rectal bleeding, colonic inflammation, edema, infiltration, crypt destruction, and higher levels of pro-inflammatory cytokines. No changes were observed in the expression levels of adhesion molecules. In conclusion, we have shown that lack of AM leads to changes in gut microbiota population and in a worsening of colitis conditions, suggesting that endogenous AM is a protective mediator in this pathology.